Good Manufacturing Practices (GMP) Implementation Training for Improving the Quality and Safety of UKM Santan XX in Batam City - Nurul Ilmi; Sadiq Ardo Wibowo; Yopy Mardiansyah; Dinda Okta Dwiyanti; Taufiq Rahman; Ronny Andri; Firstnanda Rachellia Pramiesty (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Toko Santan XX located in Nongsa District, Batam City processes coconut into coconut milk that is ready to consume by consumers. Processing is still conducted manually and a makeshift coconut grinding machine. It is not enough to support the high demand for coconut milk because Toko Santan XX has many customers in the region. In assessing the quality and safety of food management processes, Good Manufacturing Practices (GMP) studies can be used. Therefore, based on the situation analysis that has been carried out, this community service intends to provide Good Manufacturing Practices (GMP) training to Toko Santan XX. Good Manufacturing Practices (GMP) contain minimum requirements and general processing that must be met in food processing, from raw materials to final products. The purpose of the assessment is to make Toko Santan XX can create higher quality products and more efficient management. The GMP assessment was carried out using 14 assessment aspects, the average percentage was 59.45. This means that it is enough for Toko Santan XX to implement GMP at its place of business, but it still needs to be improved. Recommendations for improvements that need to be made include making SOPs based on the order of coconut milk production so that work is more organized, improving the layout of coconut milk processing tools and machines to increase productivity, and avoiding unnecessary movements. In addition, there needs to be an awareness of HSE at Toko Santan XX.